Ribose 5-phosphate isomerase B knockdown compromises trypanosoma brucei bloodstream form infectivity - Loureiro, Ines; Faria, Joana; Clayton, Christine; Macedo-Ribeiro, Sandra; Santarém, Nuno; Roy, Nilanjan; Cordeiro-da-Siva, Anabela; Tavares, Joana (PLoS neglected tropical diseases, 2015)
Ribose 5-phosphate isomerase is an enzyme involved in the non-oxidative branch of the pentose phosphate pathway, and catalyzes the inter-conversion of D-ribose 5-phosphate and D-ribulose 5-phosphate. Trypanosomatids, including the agent of African sleeping sickness namely Trypanosoma brucei, have a type B ribose-5-phosphate isomerase. This enzyme is absent from humans, which have a structurally unrelated ribose 5-phosphate isomerase type A, and therefore has been proposed as an attractive drug target waiting further characterization. In this study, Trypanosoma brucei ribose 5-phosphate isomerase B showed in vitro isomerase activity. RNAi against this enzyme reduced parasites' in vitro growth, and more importantly, bloodstream forms infectivity. Mice infected with induced RNAi clones exhibited lower parasitaemia and a prolonged survival compared to control mice. Phenotypic reversion was achieved by complementing induced RNAi clones with an ectopic copy of Trypanosoma cruzi gene. Our results present the first functional characterization of Trypanosoma brucei ribose 5-phosphate isomerase B, and show the relevance of an enzyme belonging to the non-oxidative branch of the pentose phosphate pathway in the context of Trypanosoma brucei infection.
Gesehen am 03.06.2020